Assessment of organizations readiness for networking collaboration - SADRIEV, A.R.; KAMAEV, B.N. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The paper investigates the organization’s readiness to network interaction while implementing innovation activities. The inclination to take part is being analyzed with the use of factors, including the “organization competency profile”, “organization flexibility”, “media relevance of organization data on the Internet” and “level of development of the organization’s cooperative relationships”. The process of the quantitative data is carried out with the help of the main components method, the functionality is realized with the implementation of the FactoMinerR software package. As a result, the ranked data on 109 relevant organizations, revealing their predisposition to the cooperation of the innovation network. RESUMEN El documento investiga la preparación de la organización para interactuar en red. La inclinación a participar se está analizando con el uso de factores, que incluyen el "perfil de competencia de la organización", la "flexibilidad de la organización", la "relevancia mediática de los datos de la organización en Internet" y el "nivel de desarrollo de las relaciones de cooperación de la organización". El procesamiento de los datos cuantitativos se realiza con el método de componentes principales, la funcionalidad se realiza con el paquete de software FactoMinerR. Los datos clasificados de 109 organizaciones relevantes, revelando su predisposición a la cooperación de la red de innovación.